Solubility and solubility modeling of polycyclic aromatic hydrocarbons in subcritical water - Teoh, W.; Mammucari, R.; Vieira De Melo, S.; Foster, Neil (American Chemical Society, 2013)
A static analytical equilibrium method was used to measure the binary and ternary solubilities of anthracene and p-terphenyl in subcritical water between 393 and 473 K and at 50 and 150 bar. Temperature was found to have the most significant effect on the solubility of polycyclic aromatic hydrocarbons (PAHs) in subcritical water. The effect of pressure, and the combined effect of temperature and pressure on solubility were found to be insignificant, particularly when the range of pressure considered is relatively small. The solubilities of PAHs were found to be governed primarily by sublimation pressure, and only secondarily by the dielectric constant of water. The Peng-Robinson equation of state was used to correlate the aqueous solubilities of PAHs under subcritical conditions, with good agreement between experimental and calculated values obtained for binary systems. © 2013 American Chemical Society.